2019
DOI: 10.1371/journal.pmed.1002999
|View full text |Cite
|
Sign up to set email alerts
|

Intensification with dipeptidyl peptidase-4 inhibitor, insulin, or thiazolidinediones and risks of all-cause mortality, cardiovascular diseases, and severe hypoglycemia in patients on metformin-sulfonylurea dual therapy: A retrospective cohort study

Abstract: BackgroundAlthough patients with type 2 diabetes mellitus (T2DM) may fail to achieve adequate hemoglobin A1c (HbA1c) control despite metformin-sulfonylurea (Met-SU) dual therapy, a third-line glucose-lowering medication—including dipeptidyl peptidase-4 inhibitor (DPP4i), insulin, or thiazolidinedione (TZD)—can be added to achieve this. However, treatment effects of intensification with the medications on the risk of severe hypoglycemia (SH), cardiovascular disease (CVD), and all-cause mortality are uncertain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Studies suggested that thiazolidinediones had a higher risk of hypoglycemia when used in combination with other types of antidiabetic drugs, especially insulin and sulfonylureas 28 . This study supported the conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggested that thiazolidinediones had a higher risk of hypoglycemia when used in combination with other types of antidiabetic drugs, especially insulin and sulfonylureas 28 . This study supported the conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…The database has been used in previous studies involving long-term follow-up of patients treated with various anti-diabetic medications. 15 , 16 , 17 Patients with type 2 diabetes managed in the HA public health clinics receive regular diabetic complication screening. During each diabetic complication screening session, patients are assessed clinically and have laboratory investigations to determine their control of diabetes, its related cardiovascular risk factors and the presence of diabetic complications.…”
Section: Methodsmentioning
confidence: 99%
“…HA database has been extensively used for conducting high-quality large population-based studies (24)(25)(26) . The diagnosis of diabetes mellitus was identified by the International Classification of Primary Care, Version 2 (ICPC-2) codes T89/T90 or International Statistical Classification of Diseases and Related Health Problems, 9th Revision, Clinical Modification (ICD-9-CM) codes 250.x.…”
Section: Study Design and Data Source Descriptionmentioning
confidence: 99%